Grayscale patterning of PEDOT: PSS films by multi-photon lithography - Yao, Xiao (Kansas State University, 2008)
Lithography techniques have been widely used to fabricate optical, electronic and optoelectronic devices with sub-micron scale spatial resolution. In the most common lithographic procedures, a light sensitive polymer, called a photoresist, is exposed and developed to form a binary relief pattern on a substrate. The finest features are produced by X-ray or electron-beam methods, both of which are very expensive to employ. Less expensive methods use ultraviolet (UV) light to expose the photoresist through a photomask. The resolution in these methods is somewhat lower and is governed by diffraction of light by the photomask, the quality of the photomask, and by any chemical/physical development steps subsequently employed. Due to the above limitations, we have been investigating direct-write, ablative multiphoton lithography as an alternative method for preparing high-resolution patterns. With this method, near-IR light from an ultrafast pulsed laser source is focused into a polymer film, leading to depolymerization and vaporization of the polymer. Arbitrary binary patterns can be produced by raster scanning the sample while controlling exposure of the film to the laser. Importantly, high-resolution etching of the polymer film is achieved without the use of a photomask and without chemical development steps. While arbitrary patters are easily prepared, it is also possible to prepare three-dimensional (i.e. grayscale) surface relief structures. In this study, ablative multiphoton photolithography is used to prepare binary and grayscale structures in thin films of PEDOT:PSS, an electrically conductive organic polymer blend. A simple kinetic model is proposed to explain the etching process. Data on the power-dependence of polymer etching can be fit to this model and is used to determine the order of the nonlinear optical process involved. The etch depth as a function of laser focus is also investigated and shown to follow the same kinetic model. The results show that three-dimensional (grayscale) patterns can be prepared by modulating either the laser power or the laser focus. Images of several binary and grayscale structures prepared by this method are presented.
Keywords: Grayscale patterning; Multiphoton lithography; PEDOT:PSS films; Chemistry, Analytical (0486)